Multivariable generalized state-space receding horizon control in a real-time environment - Gambier, Adrián; Unbehauen, Heinz (Automatica, 1999)
The results of a multivariable generalized state-space receding horizon control, applied to a turbo-generator pilot plant, are reported in this paper. The control algorithm consists of a state-space receding horizon tracking system, a compensator for piecewise constant random disturbances, and a state and disturbances estimator based on an augmented Kalman filter. The turbo-generator consisting of a turbine and a synchronous generator exhibits nonlinear and nonminimum-phase behaviour in a stochastic environment.